Foreign-born Germans in the United States: where are they migrating and why? - Henning, Sabine (ERDKUNDE, 1999)
Although German immigrants do not dominate current migration streams directed toward the United States anymore, foreign-born Germans remain a numerically important segment of the foreign-born population stock in the United States. Using 1990 Census data, this paper sets out to describe internal migration streams of foreign-born Germans from an accounting perspective for the 1985-1990 time period. This is followed by an analysis of the determinants of the internal migration patterns applying logistic regression techniques. The goal is to test for the relevance of the economic theory in migration (i.e., human capital theory) and to test if social capital factors (i.e., social capital theory) influence migration decisions. The investigation describing the migration patterns reveals that foreign-born Germans display indeed distinct preferences to migrate to certain states or remain in others. The analysis focusing on the determinants of migration points out that human capital factors, such as education, strongly influence migration decisions. In addition, social capital, such as networks of foreign-born Germans in the states under consideration, acts as strong deterrents to interstate migration flows.